MASYARAKAT DAERAH ALIRAN SUNGAI CODE DALAM MENANGGULANGI DAMPAK BENCANA BANJIR - Ermawan Susanto (Jurnal Penelitian Humaniora, 2010)
This research aims at empowering DAS’s (river flowing area) people at the village of Code Jetis, Yogyakarta in covering flood disaster and in giving assistance of flood disaster emeregency. The design of research uses qualitative descriptive design which is done by using survey method. The method of data collection uses data triangulation which consists of: (1) Focus group discussion of local people (3 citizens), ad (2) non participant observation in DAS setting at Code. Subject of research that is used here is people at DAS of Code which consists of young people or public figure and expert as facilitators where live at Jogoyudan, Gondolayu, Gedongtengen, and Gowongan. Instrument of research is the researcher which is in this case helped by theme list that has prepared. The theme list is prepared by research team before FGD even. Data at FGD is recorded using audio tape and transmitted. Non-participant Data was notes on field-notes. The first Data analytic is data reduction,when transcript notes and field-notes reducted due the first topic and appear topic during taking of data. Furthermore, the process are data reconstruction and analisis thematic. The result of FGD process did doing for two groups untuil second group, then not found of new topics til the topic was same. The people live in Jetis said that antisipation and victim handling especially overflow is more benefit. Although some people was complication to knowing victim handling for drowning and near drowning because that knowledge is not enough.